Genetic and taxonomic relationships of five species of Rallidae (Aves: Gruiformes) based on mitochondrial cytochrome oxidase subunit I sequences (Acta Scientiarum. Animal Sciences, 2018)
This is the first study to detection the genetic relationship between Porphyrio alleni and four Rallidae species: Fulica atra, Gallinulla angulata, Gallinulla chloropus and Porphyrio porphyrio. Mitochondrial cytochrome oxidase subunit I (COI) sequences were used as an effective marker in this study. DNA of Rallidae species were extracted, amplified using polymerase chain reaction (PCR) and then sequenced. The results obtained from information based on COI sequences revealed that Gallinulla angulata and Gallinulla chloropus fall into two separate clades and they are not monophyletic. This suggests that, two moorhens could not be laid into the same genus. In addition, Porphyrio porphyrio was included in the same genus with Porphyrio alleni but they were situated in two different clades. Porphyrio alleni was more related to Gallinulla angulate, Gallinulla chloropus and Fulica atra than Porphyrio porphyrio. It was concluded that, the mitochondrial gene COI can aid in the differentiation of studied species and finding genetic relationships between them.